2020
DOI: 10.1039/d0fd00020e
|View full text |Cite
|
Sign up to set email alerts
|

Playing the blues, the greens and the reds with cellulose-based structural colours

Abstract: Structural vivid colours can arise from the interference of light reflected from structures exhibiting periodicity on scales in the range of visible wavelengths. This effect is observed with light reflected...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Evaporation drives the diffusion of the two solvents from inside of the quasi-2D samples to the outside. We recall that in previous work with 1D systems (flat capillaries) similar diffusion toward the two menisci was observed 32 . For the same interval of time, the colours of the quasi-2D samples change significatively during the first 8 days, unlike the precursor L-handed solutions in vials.…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…Evaporation drives the diffusion of the two solvents from inside of the quasi-2D samples to the outside. We recall that in previous work with 1D systems (flat capillaries) similar diffusion toward the two menisci was observed 32 . For the same interval of time, the colours of the quasi-2D samples change significatively during the first 8 days, unlike the precursor L-handed solutions in vials.…”
Section: Resultssupporting
confidence: 65%
“…The observed behaviour cannot however be attributed solely to the diffusion of the solvent. The chemical reaction that can occur between the TFA and the cellulosic chain must also play a crucial role, as was identified for the 1D geometry and other cellulosic systems 11,32 . One of the products that results from the chemical esterification of HPMC is water.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…, , To explain the reverse of the handedness of the chiral nematic supramolecular helicoidal structure a conformational self-arrangement of the cellulosic chain was considered [23]. Similar behaviour was observed for samples encapsulated in capillaries [32].…”
mentioning
confidence: 75%
“…CNC suspensions have related optical properties because of their chiral nematic structure, 17 which can be retained in CNC films and results in a structured color after the water evaporates 18,19 . Many studies have shown that by changing the magnetic field intensity, 20 the starting concentration, 21 the solvent, 22,23 the evaporation rate, 24 the evaporation temperature, 25 the particle size, 26,27 the surface charge, 28 and the ionic strength of the liquid, 29 the pitch can be manipulated to adjust the structure color of the film. With a safe and stable structural color, CNCs can be modified or combined with other compounds to prepare light, heat, pH, humidity, or gas sensitive films 30–35 .…”
Section: Introductionmentioning
confidence: 99%